2019
DOI: 10.1111/gcbb.12615
|View full text |Cite
|
Sign up to set email alerts
|

Winter hardiness of Miscanthus (III): Genome‐wide association and genomic prediction for overwintering ability in Miscanthus sinensis

Abstract: Overwintering ability is an important selection criterion for Miscanthus breeding in temperate regions. Insufficient overwintering ability of the currently leading Miscanthus biomass cultivar, M. ×giganteus (M×g) ‘1993–1780', in regions where average annual minimum temperatures are −26.1°C (USDA hardiness zone 5) or lower poses a pressing need to develop new cultivars with superior cold tolerance. To facilitate breeding of Miscanthus, this study characterized phenotypic and genetic variation of overwintering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…For example, in Miscanthus, another well-known bioenergy biomass crop, substantial phenotypic variations of overwintering ability (i.e. transition from winter dormancy to spring regrowth, a trait analogous to spring green-up in this study) have been reported in a large M. sinensis germplasm panel (Dong et al 2019a), and QTL mapping across multiple populations revealed numerous QTLs that are unique to speci c populations (Dong et al 2018;Dong et al 2019b). Therefore, more genetic mapping studies are needed to understand the rich genetic diversity underlying agronomic traits in switchgrass, particularly the underexplored yet important traits such as spring green-up and plant vigor.…”
Section: Introductionmentioning
confidence: 63%
“…For example, in Miscanthus, another well-known bioenergy biomass crop, substantial phenotypic variations of overwintering ability (i.e. transition from winter dormancy to spring regrowth, a trait analogous to spring green-up in this study) have been reported in a large M. sinensis germplasm panel (Dong et al 2019a), and QTL mapping across multiple populations revealed numerous QTLs that are unique to speci c populations (Dong et al 2018;Dong et al 2019b). Therefore, more genetic mapping studies are needed to understand the rich genetic diversity underlying agronomic traits in switchgrass, particularly the underexplored yet important traits such as spring green-up and plant vigor.…”
Section: Introductionmentioning
confidence: 63%
“…Given that population structure can inflate genomic prediction accuracies (Guo et al, 2014; Riedelsheimer et al, 2012), we accounted for sub‐structure in the M. sacchariflorus germplasm panel by fitting a linear model where the trait LS means were the response variable, and the genetic groups were the explanatory variable using Equation (4):ygoodbreak=μgoodbreak+Dgoodbreak+e,where y is the LS means calculated from Equations (1) or (2), μ is the grand mean, D is the genetic group of M. sacchariflorus previously identified by Clark et al (2018) for this diversity panel, and e is the residual effect. The residuals from the model were used as phenotypic values in genomic prediction as previously done in Clark, Dwiyanti, et al (2019), Dong et al (2019) and Lipka et al (2014). We performed genomic prediction for each trait, and all 590 accessions, with LS means estimated for ZJU, northern locations (HU + UI + KNU), and all locations (HU + UI + KNU + ZJU).…”
Section: Methodsmentioning
confidence: 99%
“…Previous GWAS and genomic prediction efforts in Miscanthus have focused on M. sinensis (Clark, Dwiyanti, et al, 2019; Davey et al, 2017; Dong et al, 2019; Nie et al, 2016; Slavov et al, 2014; Teng et al, 2017; Zhao, Wang, et al, 2013). However, GWAS and genomic prediction have been largely unexplored in M. sacchariflorus , with only two prior studies in the literature (Clark et al, 2016; Olatoye et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Miscanthus has been considered to be a promising second-generation bioenergy crop [ 15 ]. The genus is naturally distributed in a wide climatic range from tropical areas of east Asia to ~50 °N in eastern Russia [ 16 , 17 ]. Therefore, Miscanthus species have extensive genetic diversity for energy crop development.…”
Section: Introductionmentioning
confidence: 99%